IEEE/WIC/ACM International Conference on Intelligent Agent Technology
DOI: 10.1109/iat.2005.54
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Markets for Efficient Energy Management

Abstract: The deregulation of the electricity industry in many countries has created a number of marketplaces in which producers and consumers can operate in order to more effectively manage and meet their energy needs. To this end, this paper develops a new model for electricity retail where end-use customers choose their supplier from competing electricity retailers. The model is based on simultaneous reverse combinatorial auctions, designed as a second-price sealed-bid multi-item auction with supply function bidding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…For instance, renewable energy grew by 66.4% in 2012 in the Brazilian market [7], and by 60% in 2013 in the Spanish market [3]. In some countries, such as Brazil and Germany, a good portion of electricity is generated from wind energy, which has almost no marginal costs [8]. Consequently, wind is preferred to other energy sources [8].…”
Section: Scope and Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, renewable energy grew by 66.4% in 2012 in the Brazilian market [7], and by 60% in 2013 in the Spanish market [3]. In some countries, such as Brazil and Germany, a good portion of electricity is generated from wind energy, which has almost no marginal costs [8]. Consequently, wind is preferred to other energy sources [8].…”
Section: Scope and Problemmentioning
confidence: 99%
“…In some countries, such as Brazil and Germany, a good portion of electricity is generated from wind energy, which has almost no marginal costs [8]. Consequently, wind is preferred to other energy sources [8]. It has also been shown that the entry of new energy sources into the markets is a catalyst for economic growth [3].…”
Section: Scope and Problemmentioning
confidence: 99%
See 3 more Smart Citations